Evaluation of Workload and User Preference in a Smart Walker with Augmented Reality: A Study in Competitive and Individual Scenarios - Oliveira, Weslley; Loureiro, Matheus; Bezerra, Marcio; Machado, Fabiana; Mello, Ricardo; Segatto, Marcelo; Frizera, Anselmo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
The global aging population has increased the de-mand for rehabilitation solutions that address motor impairments and improve quality of life. However, traditional rehabilitation often struggles with low patient engagement due to the repetitive and monotonous nature of tasks. To address this, immersive technologies like mixed reality and competitive elements have been explored as strategies to enhance motivation. This study evaluated user workload, cybersickness, and scenario preference during tasks with a smart walker in an augmented reality environment, comparing competitive and individual conditions. Six participants performed object collection tasks under both scenarios. Performance metrics (task time, distance traveled, and average speed) and subjective workload (NASA-TLX) were assessed. Cybersickness symptoms were measured using the Vir-tual Reality Sickness Questionnaire (VRSQ), and an open-ended question captured participants' scenario preferences. Results showed that the competitive scenario increased mental demand by 133.5 % and perceived effort by 56.96 %. Despite the higher workload, all participants preferred the competitive scenario. The individual condition, in contrast, resulted in an 11.17% increase in physical demand and 43.4% more frustration. A learning effect was also observed. These findings suggest that, although competitive elements increase cognitive load, they can significantly enhance motivation and engagement.